Dementia and the history of disease in older adults in community - Yuan Wang; Honglian Xu; Zihan Geng; Guiling Geng; Feng Zhang (BMC, 2023)
Abstract Introduction Many studies have revealed the effect of medical history on dementia. The aim of this study was to explore the relationship between the history of disease and onset of dementia. Methods This was a multi-center, cross-sectional study, with 2595 older adults enrolled. The onset of dementia was evaluated with Revised Hasegawa Dementia Scale (HDS-R). The diagnosed diseases after the age of 40 of the participants were investigated, including respiratory system diseases, digestive system diseases, cardiovascular diseases, endocrine disorders, genitourinary system diseases, nervous system disease, sensory system diseases, dental/oral diseases, bone/joint diseases and mental illnesses. Results Data of 2458 older adults were analyzed. Univariate analysis showed that diabetes, thyroid disease, mental illness, hearing loss, stroke, dental/oral disease, Denture use, fracture/osteoporosis, kidney disease and number of diseases were risk factors for dementia. After controlling for demographic sociological variables, diabetes, dental/oral disease, and denture use were independent risk factors for dementia. Thyroid disease (P = 0.313), mental illnesses (P = 0.067), hearing loss (P = 0.595), stroke (P = 0.538), fractures/osteoporosis (P = 0.069), kidney disease (P = 0.168) were no longer significant to dementia. Conclusion Diabetes, dental/oral disease and denture use were main risk factors for dementia.